The livery collar in late medieval England and Wales politics, identity and affinity - Ward, Matthew (The Boydell Press, 2016)
The livery collar had a pervasive presence in late-medieval England. Worn about the neck to denote service to a lord, references to the collar abound in government records, contemporary chronicles andcorrespondence, and many depictions of the collar can be found in illuminated manuscripts and on church monuments. From the fifteenth century the collar was regarded as a powerful symbol of royal power, the artefact associating the recipient with the king; it also played a significant function in the construction and articulation of political and other group identities during the period. This first book-length study of the livery collar examines its cultural and political significance from the late fourteenth to the early sixteenth centuries, in particular between 1450 and 1500, the period associated with the Wars of the Roses. It explores the principal meanings bestowed on the collar, considers the item in its various political contexts, and places the collar within the sphere of medieval identity construction. It also investigates the motives which lay behind its distribution, shedding new light on the nature and understanding of royal power at the time. Matthew Ward teaches medieval history at the University of Nottingham